3 - The phenomenon of social conversion among farmers in France: From traditional agriculture to the Spirulina superfood - Philippe Stéfanini,; Samuel Ravatua-Smith, (African Sociological Review, 2015)
The purpose of this paper is to shed light on the phenomenon of social conversion that occurs when farmers change from traditional agricultural practices towards a less well-known form of aquaculture: the production of the Spirulina superfood (Arthrospira platensis). Certain farmers in southeast France converted their professional lifestyles and started producing the greenish alimentary bacteria known as Spirulina. It is often referred to as blue-green algae, but it is actually a cyanobacteria with nutritional, environmental, agricultural and therapeutic benefits. Through interviews and surveys with local farmers, we use a qualitative approach to analyzing the overall impact that occurs when farmers engage in life-changing professional conversions. The results from our analyses highlight a general phenomenon that occurs among farmers referred to as “social conversion”.In general, the research provides useful insights about the cycle of social conversion and it’s impact on farmers from professional, social and ethical perspectives.